Ecology from the Perspective of Islamic Education: A Study of Kauniyah Verses and Their Relevance to the Green Curriculum - Redho Syam, Aldo; Alwi Yusron, Moh (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2025)
The global ecological crisis is a pressing contemporary issue that demands immediate attention across various sectors, including education. Within the context of Islamic education, ecological values are deeply embedded in the teachings of the Qur’an through kauniyah (cosmic) verses that depict the order of nature and human responsibility as stewards (khalifah) on Earth. This study aims to examine the ecological principles within Islamic teachings and assess their relevance to the development of a green curriculum based on Islamic values. The main focus is to understand how kauniyah verses can serve as a conceptual foundation in formulating an Islamic education curriculum that is responsive to environmental issues. This research employs a qualitative approach using library research methods, in which data were collected through literature reviews of the Qur’an, the tafsir of Ibn Kathir, scholarly journals, Islamic education texts, and educational policy documents from international institutions such as UNESCO. The data were analyzed descriptively and qualitatively by classifying kauniyah verses related to ecology and examining their integration into the Islamic educational curriculum. The findings indicate that Islam offers a comprehensive ecological worldview encompassing principles such as khalifah (vicegerency), amanah (trust), mīzān (balance), and iṣlāḥ (restoration). These values can be integrated into the curriculum through interdisciplinary learning, the strengthening of environmental character education, and the promotion of spiritual-ecological habits. A green curriculum grounded in Islamic values can serve as a strategic solution to cultivate a generation that is not only intellectually competent but also environmentally responsible as part of their devotion to Allah SWT.